Efecto de la reubicación de nidos en el éxito reproductivo de la tortuga marina Lepidochelys olivacea (Testudinata: Cheloniidae) - Sandoval Ramírez, José Luis; Solana Arellano, Elena; Flores Garza, Rafael; Flores Rodríguez, Pedro; García Ibañez, Sergio; Castro Mondragón, Himmer (Revista de Biología Tropical, 2021)
Summary. Introduction: To increase the number of sea turtle hatchlings, it is necessary to improve conservation strategies, such as nest incubation in hatchery conditions that counteract the effects of extreme weather conditions. Objective: To compare five reproductive success parameters (hatching success, undeveloped eggs, dead hatchlings, embryonic mortality, and incubation period) of the sea turtle Lepidochelys olivacea. Methods: The incubation of nests was evaluated under two periods of nest relocation (P1 and P2) under hatchery condition, in 2018 in Guerrero, Mexico. Results: Significant differences were found in hatching success and embryonic mortality between nest relocation periods (P <0.001). In P1, lower values ​​of hatching success (77.0% P1 vs 88.6% P2) and higher values ​​of embryonic mortality (13.7% P1 vs 3.3% P2) were observed compared to those of P2. No differences were found between periods regarding the parameters undeveloped eggs, dead hatchlings and incubation period. Conclusions: The differences between the most extreme or hot environmental conditions during the first period of nest relocation seem to affect the hatching success and embryonic mortality of L. olivacea. Therefore, it is important to take action on this during this incubation stage.